Envelhecimento, antropometria dos pés e pressões plantares em idosos - Aurichio, Thaís Rabiatti (2016)
Many studies note the anthropometric and postural differences of elderly feet compared with young feet, which may be responsible for the inappropriate use of footwear by older people. The types and characteristics of footwear affect de plantar pressures during gait and, if abnormal can cause foot pain and functional disability in this population. The aim of this study was verify the influence of aging on anthropometric and postural variables of elderly feet over a period of eight years (Manuscript I), and evaluate the foot anthropometry and plantar pressures during the use of different types of usual elderly footwear, with and without foot pain (Manuscript II). In the first study, 47 older people with average age of 76 (5.18) years were evaluated at three time points over eight years. In the second study 31 elderly women with average age of 75.9 (5.6) years were evaluated the foot anthropometry, the foot pain and the plantar pressures during the use of habitual footwear, with the Pedar system (Novel Eletronics, Munich, Alemanha). The values assigned to the characteristics of their footwear were also assessed. Appropriate statistical analyzes were conducted using the SPSS 17.0 software. There are subtle anthropometric differences in elderly feet, which suggests that intergenerational differences showed by literature to occur just prior to the study period. Older women who use flats have higher overload at hindfoot, and those with foot pain have less force at hallux during gait propulsion and higher force at midfoot. These women assign lower values to the walk, fit and comfort of their shoes. Footwear industries should produce specific products for the older people, with modern and functional design and flexible materials that contribute to the fit and comfort of the feet during gait.